MUNASABAH AYAT DALAM SURAH AL-QALAM PERSPEKTIF SEMITIC RHETORICAL ANALYSIS (SRA) - Sujiat Zubaidi; Dini Amalia Fattah; Aqdi Rofiq Asnawi (Universitas PTIQ Jakarta, 2023)
The purpose of this research is to examine whether the structure of Surah Al-Qalam exhibits symmetry in accordance with patterns of parallel, concentric, or mirror-symmetrical arrangements at various levels of the text. The research methodology employs analysis, which is used to process data and address the research questions. This research approach adopts the concept of